Peran Lembaga Alternatif Penyelesaian Sengketa (LAPS) dalam Penyelesaian Sengketa Margin Trading - Novita, Dwi; Mujib, Abdul (Fakultas Syariah INSURI Ponorogo, 2023)
The background of this research is that the capital market is also able to provide real benefits for investors, where in the capital market, parties who have excess funds can meet with parties who need funds with certain agreements so that mutually beneficial reciprocity occurs, one of the parts is margin trading. Basically, no one wants disputes with other people. However, in a business relationship or an agreement, each party must anticipate the possibility of a dispute arising at any time in the future, especially in the world of capital markets, so what is the margin trading system like? and what is the role of the Alternative Dispute Resolution Institution (LAPS) in resolving margin trading disputes? on the capital market dispute itself. The type of research used in this study is library research, which is a study whose data sources are obtained from written sources, including books, laws, journals, encyclopedias, the internet, and other written works related to object under study. The approach used in this research is normative juridical, namely studying and testing secondary data in the form of positive law. This research yields, first, margin trading is capital for investors to gain greater profits through stocks that are rising in value when they themselves do not have enough funds to buy. In addition, they will also be charged interest on the loan. In the event of default or default, the consequence is that share ownership is automatically liquidated to cover losses. One of them is forced selling. Second, in the realm of civil law, there are several ways of resolving disputes which in general are through litigation (using formal court channels) and through alternative dispute resolution.